Micropropagation, antioxidant and antimicrobial activities of Asparagus officinalis Cv. Mary washington in vivo and in vitro / Arash Khorasani Esmaeili - Esmaeili, Arash Khorasani (2012)
In recent years there has been renewed interest in natural medicines that are obtained from plant parts or plant extracts. Asparagus officinalis is a herbaceous perennial plant that belongs to Liliaceae family, a valued vegetable for its medicinal properties. The present study was carried out in order to establish an efficient in vitro propagation protocol for Asparagus officinalis. For this purpose, the nodal explants of Asparagus officinalis Cv. Mary Washington were cultured on MS medium containing 3% sucrose and different concentrations of NAA and BAP or IBA and Kn, mixed or separately with range of 0-1.5 mg/l for BAP/Kn and 0-0.5 mg/l for NAA/IBA in order to obtain callus, shoot and root formation. In this study, indirect organogenesis was tested under 2 different conditions (In light and in dark) for the regeneration of Asparagus officinalis in vitro. After 6 weeks of culture the results showed that 100% of callus formation in 17 of treatments under dark and 3 treatments under light condition. So between dark and light condition, dark condition was found to be more efficient than light condition in promoting callus formation. Also among the two groups of hormones (BAP + NAA, Kn + IBA concentrations), Kn + IBA was reported to be more efficient that BAP + NAA in promoting callus formation. Results also showed that the highest average number of shoots (4.25) of size 4 mm or more per explant, formed under dark condition using 1.5 mg/l BAP mixed with 0.05 mg/l NAA. The formed shoots under dark condition were less developed, with abnormal thick and yellow color compared with the shoots produced under light condition. In light condition the highest average numbers of shoots (3.63) of size 4 mm or more per explant were found on the MS medium supplemented with 0.8 mg/l BAP alone, not in combination with NAA. Rooting was best induced in shoots excised from shoot cultures which were proliferated on MS medium supplemented with an optimal concentration of 0.4 mg/l IBA (2 roots per explant). In the second part of the study the antioxidant and antibacterial activities of ethanolic extracts of in vivo grown Asparagus officinalis cv. Mary Washington were investigated using superoxide dismutase, erythrocyte haemolysis and 2,2- diphenyl-1-picrylhydrazil free radical scavenging methods. The measured antioxidant and antimicrobial potential were then compared with the activities shown by the ethanolic extracts of in vitro grown A. officinalis as well as ethanolic extract of undifferentiated callus cells of A. officinalis produced on Murashige and Skoog medium containing 1.5 mg/l 6-benzylaminopurine combined with 0.5 mg/l naphthalene acetic acid. The highest antioxidant capacity was obtained from the in vivo grown plant extract followed by in vitro grown plant extract in all three examined assays. Although, no antibacterial activity was detected from both in vivo and in vitro grown plant extracts in the disc diffusion antimicrobial assay, ethanolic extract of A. officinalis offered antibacterial activity against Bacillus cereus.